2022
DOI: 10.3389/fenvs.2022.904254
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Digital Economy on PM2.5 Pollution: The Role of Technological Innovation in China

Abstract: PM2.5 emission causes serious harm to health and hinders the sustainable development of economy and society. Among all the factors affecting PM2.5 pollution, the role of new economic forms and information technology innovation is lacking. This study aims to explore the impact of digital economy on PM2.5 pollution and its influencing mechanism using data from 281 prefecture-level cities from 2011 to 2016. The empirical results demonstrate that digital economy is conducive to reducing PM2.5 pollution. In other w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Such as Zhou et al ( 2021 ) believed that the digital economy can reduce haze pollution via the path mechanism of enhancing the proportion of advanced industrial structure in GDP. Sun et al ( 2022 ) confirmed that the digital economy promoting innovation is an important mediation mechanism that affects PM2.5 pollution through the mediation effect model.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Such as Zhou et al ( 2021 ) believed that the digital economy can reduce haze pollution via the path mechanism of enhancing the proportion of advanced industrial structure in GDP. Sun et al ( 2022 ) confirmed that the digital economy promoting innovation is an important mediation mechanism that affects PM2.5 pollution through the mediation effect model.…”
Section: Literature Reviewmentioning
confidence: 97%
“…These advancements are closely associated with green, low-carbon development, playing a crucial role in pollution mitigation. Numerous studies [30][31][32] have highlighted the digital economy's role in fostering the development of cleaner technologies and greener products. This is facilitated through the promotion of scientific and technological innovations, especially patents in green technology.…”
Section: Hypothesesmentioning
confidence: 99%
“…Recent studies have indicated that the development of the digital economy significantly impacts the reduction in PM 2.5 pollution [27]. The influence of the digital economy on PM 2.5 is primarily mediated through key factors, such as urban quality development and land use planning [28][29][30][31][32]. The exact manner in which the digital economy affects PM 2.5 pollution is not yet fully understood, necessitating further research to elucidate its mechanisms comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of environmental supervision, the digital economy can utilize information technology to achieve real-time monitoring of various pollutants and pollution sources. In particular, smart monitoring systems play a crucial role in encouraging polluting firms and industries to effectively control and eliminate excessive pollutant emissions, thereby achieving environmentally friendly production and reducing carbon pollution [15]. From the perspective of macro-governance, the government can leverage digital technology to acquire a better comprehension of energy trade direction and price oscillations.…”
Section: The De and Carbon Pollutionmentioning
confidence: 99%